Midterm outcomes after aortic valve neocuspidalization with autologous pericardium. Single center experience. (14th October 2021) - Semagin, A P; Zybin, A A; Karpushkina, E M; Shubin, E I
Abstract: Objective: The aim of the study was to analyze the midterm results of the aortic valve neocuspidalization with autologous pericardium. Methods: From August 2017 through October 2018, 40 patients were treated with aortic valve neocuspidalization using autologous pericardium, their medical records were retrospectively reviewed. Results: There were 40 patients (19 males, 21 females) with aortic stenosis, 17 patients had bicuspid valve. The median age was 66 (26–77) years. Preoperative echocardiography revealed a peak pressure gradient had mean value of 84.5±23.32 mm Hg, and mean pressure gradient average of 48.2±16.4 mm Hg. Surgical annular diameter was 21.2±2.16 mm. Body mass index was 29.7±3.4 kg / m 2 . Severe patient-prosthesis mismatch was predicted in 18 cases, moderate – in 14 cases (Hancock II prosthesis was used as a reference). Intraoperative control of neocuspidalized valve (coaptation, pressure gradient) was performed with transesophageal echocardiography. There was no conversion to a prosthetic valve replacement. There were no in-hospital mortalities. Postoperative echocardiography revealed a peak pressure gradient mean value of 16.3±5.3 mm Hg, and mean pressure gradient average of 8.5±3.1 mm Hg on the 5th postoperative day, the mean height of coaptation was 12.3±3.1 mm. Mean observation period was 17 months. During the observation period 4 (10%) patients died from non-surgery related causes. 1-year after surgery echocardiography revealed a peak pressure gradient mean value of 14.5±5.0 mm Hg, and mean pressure gradient average of 9.2±4.0 mm Hg, mild-to-moderate (grade 2) aortic insufficiency was identified in two patients. Reoperation was required in one case – patient was found to have severe aortic regurgitation due to rupture of the commissural suture. Conclusion: Our short-term and mid-term results demonstrate satisfactory neovalves' hemodynamic performance. The simplicity and reproducibility of aortic valve reconstruction with autologous pericardium may make this method an option for surgical treatment of aortic valve diseases. FUNDunding Acknowledgement: Type of funding sources: None.